Immediate, Early, and Conventional Implant Placement in a Patient with History of Periodontitis - Alessandro Lanza; Fabio Scognamiglio; Felice Femiano; Michele Lanza (Case Reports in Dentistry)
The aim of this paper is to describe a case of implant-prosthetic rehabilitation in a patient with periodontitis, focusing on the different timing of implant placement. After initial periodontal treatment, teeth with advanced mobility degree and severe bone resorption were extracted. At different healing time oral implants were placed in a prosthetic-guided position. After osseointegration period the implants were loaded and the results at one year of follow-up are presented.